20-Deoxyingenol alleviates osteoarthritis by activating TFEB in chondrocytes. (March 2021) - Gu, Mingbao; Jin, Jie; Ren, Chenghao; Chen, Ximiao; Pan, Zongyou; Wu, Yaosen; Tian, Naifeng; Sun, Liaojun; Wu, Aimin; Gao, Weiyang; Zhou, Yifei; Lin, Zhongke; et al.
Graphical abstract: Abstract: Osteoarthritis (OA) is an age-related degenerative disease and currently cannot be cured. Transcription factor EB (TFEB) is one of the major transcriptional factors that regulates autophagy and lysosomal biogenesis. TFEB has been shown to be an effective therapeutic target for many diseases including OA. The current study explores the therapeutic effects of 20-Deoxyingenol (20-DOI) on OA as well as its working mechanism on TFEB regulation. The in vitro study showed that 20-DOI may suppress apoptosis and senescence induced by oxidative stress in chondrocytes; it may also promote the nuclear localization of TFEB in chondrocytes. Knock-down of TFEB compromised the effects of 20-DOI on apoptosis and senescence. The in vivo study demonstrated that 20-DOI may postpone the progression of OA in mouse destabilization of the medial meniscus (DMM) model; it may also suppress apoptosis and senescence and promote the nuclear localization of TFEB in chondrocytes in vivo . This work suggests that 20-Deoxyingenol may alleviate osteoarthritis by activating TFEB in chondrocytes, while 20-DOI may become a potential drug for OA therapy.